ANALISIS CAPAIAN STANDARINDONESIAN SUSTAINABLE PALM OIL (ISPO) PEKEBUN KELAPA SAWITPOLA SWADAYA DI KABUPATEN KAMPAR - Rudy Hery Syahfutro; Syaiful Hadi; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Oil palm is one of the leading plantation commodities in Indonesia. The advantages of palm oil make Indonesia the largest producer and exporter of palm oil in the world. ISPO or Indonesia Sustainable Palm Oil is Indonesian sustainable palm oil that was formed and implemented by the provisions in force in Indonesia. ISPO provisions were drafted in 2011 with the issuance of Minister of Agriculture No.19/Permentan/OT.140/3/2011 concerning Guidelines for Sustainable Oil Palm Plantations in Indonesia and has been updated to Minister of Agriculture No. 11 of 2015. ISPO is mandatory and any violation will be dealt with. In 2020, new provisions on ISPO were drafted with the issuance of Presidential Decree No. 44 of 2020 concerning the Indonesian Sustainable Oil Palm Plantation Certification System. The purpose of this study was to analyze the level of achievement of the ISPO standard for independent oil palm smallholders in Kampar Regency. Sampling a representative area using multistage sampling. From all urban sub-districts in Kampar Regency, 3 sub-districts were selected as samples in this study, namely Tapung Hulu District, Tapung District, and TapungHilir District. There are two types of data used in this study, namely primary data and secondary data. The use of qualitative descriptive analysis in this study is to evaluate the achievement of the ISPO principles and criteria by smallholders. The results of this study indicate that independent oil palm smallholders in Kampar Regency are still not able to apply the best standards for oil palm plantations in accordance with ISPO principles, criteria and indicators. Key words: Smallholders, Independent Oil Palm, ISPO